2018
DOI: 10.3389/fnmol.2018.00418
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate, Glutamine and GABA Levels in Rat Brain Measured Using MRS, HPLC and NMR Methods in Study of Two Models of Autism

Abstract: The disorders of the glutamatergic neurotransmission have been associated with pathogenesis of autism. In this study we evaluated the impact of the in vivo and ex vivo test methodology on measurements of levels of neurotransmitter amino acids in hippocampus of rats for valproic acid- (VPA) and thalidomide- (THAL) induced models of autism. The main goal was to compare the changes in concentrations of glutamate (Glu), glutamine (Gln) and GABA between both autistic groups and the control, measured in vivo and ex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
36
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 82 publications
9
36
1
1
Order By: Relevance
“…In order to evaluate our hypothesis, it was important to establish whether the significant differences found for the positive control VPA in the existing literature were similar to the results obtained in this study, and, as we can see, we have obtained results consistent with those of other published studies regarding two of the variables: latency to the first call, and number of calls [ 30 , 31 , 32 ]. Taking this into account, and examining the data obtained from the group prenatally exposed to CPF, which showed similar results to VPA regarding the same two variables, we can assume that our hypothesis has at least been partially supported.…”
Section: Discussionsupporting
confidence: 86%
“…In order to evaluate our hypothesis, it was important to establish whether the significant differences found for the positive control VPA in the existing literature were similar to the results obtained in this study, and, as we can see, we have obtained results consistent with those of other published studies regarding two of the variables: latency to the first call, and number of calls [ 30 , 31 , 32 ]. Taking this into account, and examining the data obtained from the group prenatally exposed to CPF, which showed similar results to VPA regarding the same two variables, we can assume that our hypothesis has at least been partially supported.…”
Section: Discussionsupporting
confidence: 86%
“…Based on this data, useful models of chemically induced autism-like behavior in rodents have been developed. In our previous study, using the same VPA and THAL rat models of autism, we also observed behavioral changes similar to autism and neurochemical disruption in the brains of these animals, suggesting disturbances in glutamatergic neurotransmission (Zieminska et al 2018). We hypothesize that these abnormalities may be a reflection of dysfunction in synaptic vehicle trafficking that result from the altered expression of genes encoding some members of the protein complex SNARE, in particular the SNAP-25 protein and could be implicated in the causation of the behavioral deficits in ASD.…”
Section: Introductionsupporting
confidence: 59%
“…A major endophenotype that reflects persistent alterations in neuronal activity in mood-related disorders is the levels and neurometabolic activity of glutamate and GABA, the major excitatory and inhibitory neurotransmitters respectively 59,60,[62][63][64][65][66] . Although 1 H-MRS has been widely used to examine the levels of these neurotransmitters in both human patients and rodents 116,117 , there has been a scarcity of studies to investigate neurometabolic activity, which represent a functional readout of metabolic dynamics in these neurocircuits 118,119 . We employed H-[ C]-NMR spectroscopy to measure the metabolic rate of excitatory and inhibitory neurons in conjunction with infusion of [1,6-13 C ]glucose 67,68,118,119 .…”
Section: Discussionmentioning
confidence: 99%